Study of Skin Sensitivity to Various Allergens by Prick Skin Test in Patients with Bronchial Asthma - Hasan Alwan , Adnan; Ahamed AL-Dulaimy , Raid (Diyala Journal of Medicine, 2019)
Objective: The aim of the study is to determine the most common allergens triggering allergic disease in Diyala Governorate. Materials and Methods: This study including 391 patients (148 male and 243 female ) with bronchial asthma attending asthma and allergy unit of Baquba teaching hospital consultation clinic from 4/1/2009 to 31/12/2009. skin prick test were done for them ; the results were fixed according to the reactivity of the allergens used in the study. Results: Most common offending allergens were house dust mite( 25.3%), Bermuda 23% , grasses 19.6% , mugwart 16.6% , fagace 15.8% , chenopoda 15.6% , date palm and batulacea 12.7% , olacea 12% , house dust 11.5% , feather 9.9% , alternaria 9.2% , plantine 8.6% , aspirgillus 6.9% , clodosporium 5.3% , cat hair 4.6% , horse hair 4% , penicillinum 3.3% and dog hair 3% In the study it was also observed that patients of bronchial asthma had associated allergic rhinitis in 49.1% of cases . Conclusion: This study and other studies will definitely be helpful in identifying the most common triggering allergens causing various allergic disorders including bronchial asthma in Diyala Governorate ; and this will be helpful in the prevention of asthma and other allergic disorders.